"It's a Growing and Serious Problem:" Teaching 9/11 to Combat Misinformation and Conspiracy Theories. Issue 6 (2nd November 2021) - Berman, Daniel S.; Stoddard, Jeremy D.
Abstract: In the aftermath of the September 11th attacks, some who were unable to cope with the devastation and the failure to prevent them turned to alternative explanations as to how and why these attacks occurred. Coinciding with the growth of the internet, hyper-partisan news sources, and misinformation, a vast number of 9/11 conspiracy theories emerged and spread. During the past 20 years, these conspiracy theories became embedded in public discourse, and have slowly started to appear in classrooms, brought in by a generation of students not alive before and with limited understanding of 9/11. In this article, we attempt to explain how these conspiracy theories enter the classroom and teachers' strategies to combat them. Using a combination of theory and empirical data, we contend that 9/11 conspiracy theories remain popular and students' endorsement of them may come from their lack of information about 9/11 more generally. Additionally, we use activities from different teachers to demonstrate three approaches to combat conspiracy theories. At a time when conspiracy theories are used to inflame partisan beliefs, it is crucial to equip educators with resources to extinguish these conspiratorial flames.